Dominasi atau Kontestasi? : Relasi Negara dan Masyarakat di Desa Karangwuni di Masa Pandemi Covid-19 - Yayuk Windarti (Umbara, 2021)
The Covid-19 pandemic, which has occurred in Indonesia since March 2020, has created a crisis in society. The state began to take appropriate policies in handling the Covid-19 pandemic. The alignment of state’s policies in the economic or health sectors has been questioned. This research aims to examine the state’s practices in  delivering aid to members of society and the incoherent images about the state which results from the practice. The relationship between the state and the society was analyzed through Migdal’s framework. This autoethnographic research was conducted in Karangwuni Village, Polokarto District, Sukoharjo Regency. Data were collected through participatory observations, archival study, and in-depth interviews with various members of social groups, such as village chief, midwives, and residents who are directly affected by Covid-19. The result of this research indicated that the village has become an arena for domination contests by the state and the society. The state’s practice of delivering aid to members of society through the village government has led village authorities, health workers, and the aid beneficiaries to construct various images about the state. Apparently, the state is not the dominant actor. The image of the state that was originally coherent has been challenged as both the state and the society tend to pull out each other.